Midwifery Care for Pregnant Women with Late-Term Pregnancy - Finta isti kundarti; Eva Lisdiana; Ririn Indriani (Health and Technology Journal (HTechJ), 2025)
Late-term pregnancy occurs at 41 weeks to 41 weeks and six days of gestation. It poses potential risks to both the mother and the fetus. Appropriate management is crucial for preventing morbidity and mortality. This study aims to analyze Midwifery Care for Pregnant Women with Late-Term Pregnancy. This study employs a case study design with a comprehensive midwifery care approach for one patient. Data collection was carried out using a combination of interviews, direct observation, physical examinations, and document review. The analysis followed the structured stages of the midwifery care process, which include assessment, diagnosis, implementation, and evaluation. The case study was conducted on Mrs. YS, who did not experience signs of labor and refused induction. The diagnosis was established as G3P1011 with a gestational age of 42-42 weeks and a late-term intrauterine live fetus. The intervention involved referring the patient to the hospital for a cesarean section. The evaluation showed that the C-section went well, and the mother and baby were in good health after delivery. This case study highlights the importance of early detection and appropriate decision-making when managing overdue pregnancies. Refusing induction poses a clinical challenge requiring an educational and collaborative approach to avoid increasing the risk of maternal and neonatal complications.